1971
DOI: 10.1136/thx.26.6.734
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of azathioprine in severe chronic asthma

Abstract: Previous studies of immunosuppressive therapy in asthma have been uncontrolled and conflicting in their results. Two double-blind controlled cross-over trials using two dosage levels of azathioprine (2 mg/kg and 5 mg/kg for three and four weeks respectively) in a total of 20 patients with chronic severe asthma are described. Both objective and subjective assessments by independent observers indicated no significant change in the groups as a whole. However, in four patients, an improvement was attributed to aza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Controlled clinical studies have shown that low doses of methotrexate are an effective treatment for corticosteroidresistant asthma, although azathiopurine is not [5,18]. Cy closporin A is also reported to be of therapeutic value in patients who are corticosteroid-resistant [5,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Controlled clinical studies have shown that low doses of methotrexate are an effective treatment for corticosteroidresistant asthma, although azathiopurine is not [5,18]. Cy closporin A is also reported to be of therapeutic value in patients who are corticosteroid-resistant [5,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports show that certain immunosuppressors are effective in the treatment of bronchial asthma [5, [16][17][18][19][20]. Controlled clinical studies have shown that low doses of methotrexate are an effective treatment for corticosteroidresistant asthma, although azathiopurine is not [5,18].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are limited studies to address the effectiveness of azathioprine in patients with asthma. Azathioprine did not improve FEV 1 or reduce asthma exacerbations (96). Due to insufficient evidence, it is recommended that more clinical trials are required to investigate the effectiveness of azathioprine in asthma patients.…”
Section: Azathioprinementioning
confidence: 96%
“…Two placebo‐controlled studies were unable to demonstrate a beneficial effect of azathioprine (2–5 mg/kg daily) in asthma [ 117, 118]. These studies can be criticized, however, for the short duration of azathioprine therapy of maximal 4 weeks [ 116].…”
Section: Immunosuppressants and Antimetabolitesmentioning
confidence: 99%